Bacterial community profiles of leaves of wild and cultivated pohpohan (Pilea melastomoides (Poir.) Wedd.) plants based on a metagenomic analysis - EVRICK YONANTIKO; RIKA INDRI ASTUTI; SRI BUDIARTI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yonantiko E, Astuti RI, Budiarti S. 2024. Bacterial community profiles of leaves of wild and cultivated pohpohan (Pilea melastomoides (Poir.) Wedd.) plants based on a metagenomic analysis. Biodiversitas 25: 2996-3004. Recent studies show that fresh vegetables serve as hosts for diverse endophytic bacterial communities. In Indonesia, certain tropical plants are consumed fresh without cooking, which may raise concerns regarding human health and food safety. Pilea melastomoides (Poir.) Wedd. is a traditional food plant consumed fresh as a vegetable by the Sundanese people in Indonesia. This plant grows in the wild and can be cultivated in a standard plantation, thereby raising the question of the endophytic bacterial communities in both planting systems. Thus, this study aimed to profile the bacterial communities in wild and cultivated P. melastomoides via a metagenomic approach targeting the 16S rRNA gene. Data analysis revealed that the leaf samples collected from the cultivated plants exhibited the highest diversity, as indicated by the diversity indices of species richness based on Chao1 (0.0244), Shannon (0.0291), and species evenness based on Pielou (0.0282). The most abundant bacterial phyla identified were Firmicutes and Proteobacteria. In cultivated plants, the predominant endophytic bacteria included: Limosilactobacillus (5.38%), Escherichia/Shigella (4.96%), Bacillus (4.76%), Salmonella (3.57%), and Staphylococcus (3.57%). In contrast, certain genera of pathogenic bacteria, such as Escherichia/Shigella (15.59%), Bacillus (10.48%), Limosilactobacillus (9.00%), Salmonella (7.78%), and Listeria (5.94%), were dominant among the wild plants. The findings of pathogenic bacteria are dominated by Gram-negative bacteria, which play a role in the nitrogen, carbon, and sulfur cycles. The stable and consistent presence of endophytic bacteria in plant tissues provides opportunities for long-term studies for food safety and sustainable agricultural practice strategies. Further analysis should be conducted to confirm the virulence of these pathogens in both wild and cultivated P. melastomoides plants.